Question
upstudy study bank question image url

Factorise fully 1) \( 2 x^{2}+x-3 \) 2) \( 2 x^{2}+5 x-3 \) 3) \( 2 x^{2}-22 x+20 \) 4) \( 4 x^{2}+10 x-6 \)

Ask by Sanders Long. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

1. \( 2x^{2} + x - 3 = (x - 1)(2x + 3) \) 2. \( 2x^{2} + 5x - 3 = (2x - 1)(x + 3) \) 3. \( 2x^{2} - 22x + 20 = 2(x - 1)(x - 10) \) 4. \( 4x^{2} + 10x - 6 = 2(2x - 1)(x + 3) \)

Solution

Sure, let's factor each of the given quadratic expressions step by step. --- ### 1) \( 2x^{2} + x - 3 \) **Step 1:** Identify coefficients: - \( a = 2 \) - \( b = 1 \) - \( c = -3 \) **Step 2:** Find two numbers that multiply to \( a \times c = 2 \times (-3) = -6 \) and add up to \( b = 1 \). The numbers are **3** and **-2** because: - \( 3 \times (-2) = -6 \) - \( 3 + (-2) = 1 \) **Step 3:** Rewrite the middle term using these numbers: \[ 2x^{2} + 3x - 2x - 3 \] **Step 4:** Factor by grouping: \[ (2x^{2} + 3x) + (-2x - 3) = x(2x + 3) -1(2x + 3) \] **Step 5:** Factor out the common binomial: \[ (x - 1)(2x + 3) \] **Final Factored Form:** \[ 2x^{2} + x - 3 = (x - 1)(2x + 3) \] --- ### 2) \( 2x^{2} + 5x - 3 \) **Step 1:** Identify coefficients: - \( a = 2 \) - \( b = 5 \) - \( c = -3 \) **Step 2:** Find two numbers that multiply to \( a \times c = 2 \times (-3) = -6 \) and add up to \( b = 5 \). The numbers are **6** and **-1** because: - \( 6 \times (-1) = -6 \) - \( 6 + (-1) = 5 \) **Step 3:** Rewrite the middle term using these numbers: \[ 2x^{2} + 6x - x - 3 \] **Step 4:** Factor by grouping: \[ (2x^{2} + 6x) + (-x - 3) = 2x(x + 3) -1(x + 3) \] **Step 5:** Factor out the common binomial: \[ (2x - 1)(x + 3) \] **Final Factored Form:** \[ 2x^{2} + 5x - 3 = (2x - 1)(x + 3) \] --- ### 3) \( 2x^{2} - 22x + 20 \) **Step 1:** Factor out the Greatest Common Factor (GCF) first. All terms are divisible by **2**: \[ 2(x^{2} - 11x + 10) \] **Step 2:** Now, factor \( x^{2} - 11x + 10 \). Find two numbers that multiply to \( 1 \times 10 = 10 \) and add up to \( -11 \). The numbers are **-10** and **-1** because: - \( -10 \times (-1) = 10 \) - \( -10 + (-1) = -11 \) **Step 3:** Rewrite and factor by grouping: \[ x^{2} - 10x - x + 10 = x(x - 10) -1(x - 10) \] **Step 4:** Factor out the common binomial: \[ (x - 1)(x - 10) \] **Final Factored Form:** \[ 2x^{2} - 22x + 20 = 2(x - 1)(x - 10) \] --- ### 4) \( 4x^{2} + 10x - 6 \) **Step 1:** Factor out the GCF first. All coefficients are divisible by **2**: \[ 2(2x^{2} + 5x - 3) \] **Step 2:** Now, factor \( 2x^{2} + 5x - 3 \). Find two numbers that multiply to \( 2 \times (-3) = -6 \) and add up to \( 5 \). The numbers are **6** and **-1** because: - \( 6 \times (-1) = -6 \) - \( 6 + (-1) = 5 \) **Step 3:** Rewrite the middle term using these numbers: \[ 2x^{2} + 6x - x - 3 \] **Step 4:** Factor by grouping: \[ (2x^{2} + 6x) + (-x - 3) = 2x(x + 3) -1(x + 3) \] **Step 5:** Factor out the common binomial: \[ (2x - 1)(x + 3) \] **Final Factored Form:** \[ 4x^{2} + 10x - 6 = 2(2x - 1)(x + 3) \] --- **Summary of All Factored Forms:** 1. \( 2x^{2} + x - 3 = (x - 1)(2x + 3) \) 2. \( 2x^{2} + 5x - 3 = (2x - 1)(x + 3) \) 3. \( 2x^{2} - 22x + 20 = 2(x - 1)(x - 10) \) 4. \( 4x^{2} + 10x - 6 = 2(2x - 1)(x + 3) \)

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

Let's factorise each of the given quadratic expressions step by step! 1) For \( 2x^{2}+x-3 \), we can use the method of splitting the middle term. We find two numbers that multiply to \( 2 \cdot -3 = -6 \) and add up to \( 1 \). These numbers are \( 3 \) and \( -2 \). We rewrite the expression as \( 2x^2 + 3x - 2x - 3 \), and then factor by grouping to get: \[ (2x - 3)(x + 1) \] 2) For \( 2x^{2}+5x-3 \), we again look for two numbers that multiply to \( -6 \) (from \( 2 \cdot -3 \)) and add to \( 5 \). The numbers \( 6 \) and \( -1 \) work. So we rewrite it as \( 2x^2 + 6x - 1x - 3 \) and factor by grouping: \[ (2x - 1)(x + 3) \] 3) In \( 2x^{2}-22x+20 \), notice we can first factor out a \( 2 \): \[ 2(x^{2}-11x+10) \] Now, we need to factor \( x^{2}-11x+10 \). Finding numbers that multiply to \( 10 \) and add to \( -11 \), we get \( -1 \) and \( -10 \): \[ x^2 - 11x + 10 = (x - 1)(x - 10) \] So the complete factorisation is: \[ 2(x-1)(x-10) \] 4) Finally, for \( 4x^{2}+10x-6 \), we can first factor out a \( 2 \): \[ 2(2x^2 + 5x - 3) \] Next, we factor \( 2x^2 + 5x - 3 \) in the same way as before. The numbers \( 6 \) and \( -1 \) work again allowing us to rewrite it as: \[ 2(2x - 1)(x + 3) \] So the fully factorised forms of the expressions are: 1) \( (2x - 3)(x + 1) \) 2) \( (2x - 1)(x + 3) \) 3) \( 2(x - 1)(x - 10) \) 4) \( 2(2x - 1)(x + 3) \)

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy